The association of autoimmune disorders with inflammatory bowel disease. - Snook, J; de Silva, H; Jewell, D (1989)
Medical records of patients with ulcerative colitis (n = 858), Crohn's disease (n = 378) and coeliac disease (n = 148) were examined to determine the prevalence of associated autoimmune disorders. Of outpatient controls (n = 300), 2 per cent had at least one autoimmune disorder, compared to 7 per cent with ulcerative colitis, 2 per cent with Crohn's disease and 6 per cent with coeliac disease. Inclusion of primary sclerosing cholangitis with the autoimmune disorders increased the overall prevalence in ulcerative colitis to over 9 per cent. The results provide further indirect evidence of involvement of autoimmune mechanisms in the pathogenesis of ulcerative colitis.